Simbol Natural dalam Lirik Lagu “Di Manakah Matahariku” Karya Ebid G Ade sebagai Sarana Kreatif Penciptaan Kosakata Baru - M. Hermintoyo M. Hermintoyo (Nusa: Jurnal Ilmu Bahasa dan Sastra, 2017)
Song lyrics are created along with a tone of harmonization. The lyrics of the song as the author’s expression are created by choosing the right and aesthetic words, which fulfill elements of beauty such as poems that have diction, images, rhymes, and rhetorical means. Creative lyricist, such as Ebiet G Ade in the song "Where My Sun" utilizes the object seen, felt and heard by changing in a metaphor that is symbolically natural in the lyrics of the song. Ebiet G Ade as a creative lyricist produces new vocabulary through his previously invented songs. The creation of this new vocabulary is known as a private symbol, especially in the form of a metaphor.